2020
DOI: 10.1111/ffe.13370
|View full text |Cite
|
Sign up to set email alerts
|

On the microstructural evolution and room‐temperature creep behaviour of 9%Cr steel weld joint under prior creep–fatigue interaction

Abstract: The high‐temperature creep–fatigue (CF) interaction on the service damage of P92 welded joint was uncovered based on the evolution of local creep behaviour by nanoindentation. The creep resistance and high‐angle grain boundary (HAGB) distributions of the different regions of welded joint were investigated for the specimens under individual creep (stress relaxation [RS]), fatigue and CF loadings interrupted at lifetime fractions of 10%, 20%, 30%, 60% and 100%. According to structure evolution including the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Figure 10 also presents the values of m in all regions are increased with increasing strain rates. This observation could be resulted by the lower dislocation density, 23,24 which was contributed through the annihilation of dislocation during high-temperature CF interaction. 34,35 Moreover, the highest value of m was estimated from the crack region (fracture edge), 0.018 (rupture in the BM) for the strain rates of 0.005 s À1 , 0.013 (rupture in the BM) for the strain rates of 0.002 s À1 , and 0.013 (rupture in the FGHAZ) for the strain rates of 0.0001 s À1 .…”
Section: Nanoindentation Creep Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 10 also presents the values of m in all regions are increased with increasing strain rates. This observation could be resulted by the lower dislocation density, 23,24 which was contributed through the annihilation of dislocation during high-temperature CF interaction. 34,35 Moreover, the highest value of m was estimated from the crack region (fracture edge), 0.018 (rupture in the BM) for the strain rates of 0.005 s À1 , 0.013 (rupture in the BM) for the strain rates of 0.002 s À1 , and 0.013 (rupture in the FGHAZ) for the strain rates of 0.0001 s À1 .…”
Section: Nanoindentation Creep Behaviormentioning
confidence: 99%
“…A355 P92 steel is a kind of 9%Cr martensitic and ferritic steel and has been widely used in the ultrasupercritical generation of fossil fuel power plants due to excellent high-temperature creep strength. 22 Our previous work [23][24][25] on 9%Cr steel investigated the local creep behavior of a welded joint under CF loading at constant strain rate. The work in this paper focuses on the local creep behavior and fracture mechanism of 9%Cr steel welds under CF loading with different strain rates.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that stress relaxation can occur in the holding period during the straincontrolled CF test [9][10][11][12]. The typical stress relaxation behavior of the welded specimens during the tensile holding period (300 s) is shown in Figure 8.…”
Section: Stress Relaxation Behaviormentioning
confidence: 99%
“…Pandey et al [8] studied the formation mechanism of various microstructures in different regions of a P92 steel welded joint and found that the welding process produced a heterogeneous microstructure in the heat-affected zone (HAZ) of the welded joint. Those regions have different sensitivities to the macroscopical CF loading [9][10][11][12]. Relying on nanoindentation, Gao et al [13] investigated the remnant creep behavior of the base metal (BM), fine-grain heat-affected zone (FGHAZ), coarse-grain heat-affected zone (CGHAZ) and weld metal (WM) for a CF-tested P92-welded joint, and they found remarkable degradations in the creep resistances of the BM and FGHAZ regions.…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that the transformation and coarsening of carbides in the materials, 13 the precipitation of carbides M 23 C 6 at the austenite grain boundary, and the resulting dispersion hardening phase along both sides of the grain boundary, which significantly reduces the “recovery zone.” 14 The evolution process of carbide is the same with or without load. The damage causes the changes of internal microstructure and various phase structures 15, 16 . The application of accelerated aging experiment makes the analysis of microstructure more convenient 17 .…”
Section: Introductionmentioning
confidence: 99%